Two distinct cases with COVID‐19 in kidney transplant recipients. Issue 8 (16th May 2020) - Kim, Yaerim; Kwon, Ohyun; Paek, Jin H.; Park, Woo Y.; Jin, Kyubok; Hyun, Miri; Lee, Ji Y.; Kim, Hyun A.; Han, Seungyeup
Abstract : The fatality of novel coronavirus disease 2019 (COVID‐19) is precipitously increased in patients with underlying comorbidities or elderly people. Kidney transplant (KT) recipients are one of the vulnerable populations for infection. COVID‐19 infection in KT recipients might be a complicated and awkward situation, but there has been a lack of reports concerning this group. Herein, we demonstrated two distinct cases with different clinical progress. The first case was a 36‐year‐old man who underwent KT 3 years ago. He was diagnosed with COVID‐19 expressing relevant symptoms. Following administration of lopinavir/ritonavir and hydroxychloroquine with reduced immunosuppressant, he recovered from COVID‐19. However, the unexpected fluctuations in tacrolimus trough levels needed to be managed because of drug‐to‐drug interaction. The second case was developed in a 56‐year‐old man without any symptoms. He received a second KT from an ABO‐incompatible donor 8 years ago. He was diagnosed with COVID‐19 by screening due to exposure history. During the hospitalization period, the chest infiltrative lesion showed a wax and wane, but he successfully recovered by administration of hydroxychloroquine with azithromycin. These apparently different cases suggest that assertive screening and management could improve the clinical course. In addition, antiviral agents should be used cautiously, especially in patients on calcineurin inhibitors. Abstract : Assertive screening and management for COVID‐19 could improve the clinical course in kidney transplant recipients, and lopinavir/ ritonavir, commonly used in COVID‐19 infected patients, should be cautiously used in kidney transplant recipients with tacrolimus.